Marked variation in atherosclerotic plaque progression between the major epicardial coronary arteries . (26th April 2022) - Bax, A Maxim; Lin, Fay Y; van Rosendael, Alexander R; Ma, Xiaoyue; Lu, Yao; van den Hoogen, Inge J; Gianni, Umberto; Tantawy, Sara W; Andreini, Daniele; Budoff, Matthew J; Cademartiri, Filippo; Chinnaiyan, Kavitha; et al.
Abstract: Aims: Atherosclerosis develops progressively and worsens over time, yet event risk patterns vary in the left circumflex (LCx), right coronary artery (RCA) and left anterior descending (LAD). The aim of this analysis was to examine varying progressive disease alterations between the three major coronary arteries. Methods and results: Patients were included from a prospective, international registry of consecutive patients who underwent serial CCTA at a median interval of 3.3 years. Annual progression of quantitative total and compositional plaque volume were compared between the three coronary arteries (LCx, LAD, and RCA). Other analyses compared stenosis ≥50% and new high-risk plaque (HRP; ≥2 of the following: spotty calcification, positive remodelling, napkin-ring sign, and low-attenuation plaque) on follow-up. Generalized estimating equations and marginal Cox regression models were used to compare progression, with covariate adjustment by the baseline atherosclerotic cardiovascular disease risk score, statin use, and plaque burden. Quantitative plaque measurements were calculated in 1344 patients (age 60 ± 9 years, 57% men). Plaque progression occurred less often in the LCx (41.0%) as compared to the RCA (52.7%) and LAD (77.4%, P < 0.001). Odds for annual plaque burden increase ≥population mean were 1.98- and 1.43-fold as high in the LAD ( P < 0.001) and RCA ( P < 0.001) as compared to the LCx. Similarly, the LAD was associated with a 2.45 higher risk of progression to obstructive CAD ( P < 0.001), as compared to the LCx; with no differences between the RCA and LCx ( P = 0.13). New HRP lesions formed least often in the LCx (3.4%), followed by the RCA (8.1%) and most often in the LAD (10.1%; P < 0.001). Conclusions: Our findings reveal novel insights into varied patterns of atherosclerotic plaque progression within the LCx as compared to the other epicardial coronary arteries. These varied patterns reflect differing stages in the disease process or differing pathogenic milieu across the coronary arteries. Graphical Abstract: